KETERAMPILAN BELAJAR KELOMPOK - Tria, Beby; Ramadan, Dicky; Camanggi, Lia (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
In this day and age teachers are required to be more innovative in carrying out learning in the classroom, so that nowadays there are many various methods or ways of teachers in conveying learning. One of the things that teachers must pay attention to is group teaching skills, where these skills lead to healthy and close interpersonal relationships between students with one another. So here more emphasis is placed on good cooperation to achieve effective and efficient learning goals in the present. And the research method that the author uses is with a literature study approach, which comes from book references, and others. the components of small group and individual teaching skills, namely the skills of holding a personal approach to each student, the skills of organizing learning activities, the skills of guiding and facilitating learning, and the skills of designing and implementing learning activities. Keywords: teachers; Skills; Group